Synthesis, Molecular Docking Studies, and Antifungal Activity Evaluation of New Benzimidazole-Triazoles as Potential Lanosterol 14α-Demethylase Inhibitors - Nafiz Öncü Can; Ulviye Acar Çevik; Begüm Nurpelin Sağlık; Serkan Levent; Büşra Korkut; Yusuf Özkay; Zafer Asım Kaplancıklı; Ali Savaş Koparal (Journal of Chemistry)
Due to anticandidal importance of azole compounds, a new series of benzimidazole-triazole derivatives (5a–5s) were designed and synthesized as ergosterol inhibitors. The chemical structures of the target compounds were characterized by spectroscopic methods. The final compounds were screened for antifungal activity against Candida glabrata (ATCC 90030), Candida krusei (ATCC 6258), Candida parapsilosis (ATCC 22019), and Candida albicans (ATCC 24433). Compounds 5i and 5s exhibited significant inhibitory activity against Candida strains with MIC50 values ranging from 0.78 to 1.56 μg/mL. Cytotoxicity results revealed that IC50 values of compounds 5i and 5s against NIH/3T3 are significantly higher than their MIC50 values. Effect of the compounds 5i and 5s against ergosterol biosynthesis was determined by LC-MS-MS analysis. Both compounds caused a significant decrease in the ergosterol level. The molecular docking studies were performed to investigate the interaction modes between the compounds and active site of lanosterol 14-α-demethylase (CYP51), which is as a target enzyme for anticandidal azoles. Theoretical ADME predictions were also calculated for final compounds.